Ignition sebagai Inovasi Keramik Pada Brand Onix Pottery dengan Mitra UD. Tri Surya Keramik - Paramita, Ni Kadek Leony Widya; Wiyasa, I Nyoman Ngidep; Laba, I Nyoman; Putra, Rai Gede Wahyudi (Innovative: Journal Of Social Science Research, 2025)
This study aims to analyze creative industry-based entrepreneurship development strategies by emphasizing the optimization of Social Media Marketing (SMM) in promoting ceramic craft products through the Onix Pottery brand. Within the context of the Independent Learning Campus (MBKM) program, this activity represents applied learning, requiring students not only to understand theory but also to initiate and build their own businesses. The research method used was descriptive qualitative, with data collection techniques including interviews, observation, literature review, visual documentation, and market research using Google Trends. UD. Tri Surya Keramik was selected as a partner due to its strong track record in the ceramics industry since 1994. Onix Pottery, as a start-up, carries the "Ignition" design concept, employing a handmade approach and innovation in raw materials, a mixture of clay and sand from Mount Agung. Marketing is carried out using an SMM strategy that displays visual content of the production process to build brand awareness. This approach refers to Mahbub's (2020) view on the importance of digital transformation and supports Kotler and Keller's (2016) theory of product differentiation in increasing competitiveness. This research demonstrates that digital marketing strategies based on visual creativity and product innovation play a significant role in strengthening the position of start-up businesses in the creative industries sector. Onix Pottery serves as a concrete example of how combining craft skills, collaboration with experienced partners, and the use of social media can create sustainable economic opportunities. These findings are expected to serve as a reference for MSMEs and student entrepreneurs in building relevant and competitive brands in the digital era.